2017
DOI: 10.2131/fts.4.109
|View full text |Cite
|
Sign up to set email alerts
|

Permeability of skin to silver nanoparticles after epidermal skin barrier disruption in rats

Abstract: -To analyze the permeability of rat skin to silver nanoparticles, the dorsal skin of Sprague-Dawley rats was exposed to 5 nm Ag nanoparticles or silver nitrate (Ag + ions) percutaneously for 24 hr after disruption of the epidermal barrier by tape stripping (TS) or acetone wiping (AC). Systemic toxicity was examined hematologically and histopathologically, and by assessing blood biochemistry. Although parakeratosis, decrease in keratohyaline granule, and thickening in the epidermis occurred following exposure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…The high content of glycerol in Ia could have increased SSD penetration in our experiments. Several studies have already shown that silver (as Ag 0 or Ag + ) can penetrate through damaged skin and reach circulation in vivo 22 24 or ex vivo 25 . In addition, Larese et al observed the detectable penetration of silver from AgNP applied on intact ex vivo human skin 26 .…”
Section: Discussionmentioning
confidence: 99%
“…The high content of glycerol in Ia could have increased SSD penetration in our experiments. Several studies have already shown that silver (as Ag 0 or Ag + ) can penetrate through damaged skin and reach circulation in vivo 22 24 or ex vivo 25 . In addition, Larese et al observed the detectable penetration of silver from AgNP applied on intact ex vivo human skin 26 .…”
Section: Discussionmentioning
confidence: 99%